Numerical Experiments on Soft X-ray Emission Optimization of Nitrogen Plasma in 3 kJ Plasma Focus SY-1 Using Modified Lee Model - Akel, M.; Al-Hawat, Sh.; Lee, S. (Springer US, 2009)
The X-ray emission properties of nitrogen plasmas are numerically investigated using corona plasma equilibrium model. The X-ray emission intensities of nitrogen Lya, Lyb and Hea, Heb lines are calculated. The optimum plasma temperature for nitrogen X-ray output is concluded to be around 160 eV. The Lee model is modified to include nitrogen in addition to other gasses (H2, D2, He, Ne, Ar, Xe). It is then applied to characterize the 2.8 kJ plasma focus PF-SY1, finding a nitrogen soft X-ray yield (Ysxr) of 8.7 mJ in its typical operation. Keeping the bank parameters and operational voltage unchanged but systematically changing other parameters, numerical experiments were performed finding the optimum combination of pressure = 0.09 Torr, anode length = 7.2 cm and anode radius = 2.58 cm. The optimum Ysxr was 64 mJ. Thus we expect to increase the nitrogen Ysxr of PF-SY1 sevenfold from its present typical operation; without changing the capacitor bank, merely by changing the electrode configuration and operating pressure.